Population Differentiation and Polygenic Selection in the Finnish Ayrshire Cows Selected on Genomic Information - Sarviaho, Katri; Koivula, Minna; Iso‐Touru, Terhi; Uimari, Pekka; Hänninen, Katja (Wiley-Blackwell, 2026)
The Finnish Ayrshire cattle belong to the Nordic Red breeds. The basis of selection in Nordic Red breeds shifted from traditional pedigree-based breeding values to genomic breeding values between 2011 and 2014. Joint genetic evaluation and admixture among the Nordic Red breeds have led to the formation of a composite Nordic Red population; consequently, contemporary Finnish Ayrshire represents an admixed population. We identified recent selection signatures in the Finnish Ayrshire genome using two complementary approaches: the Hudson estimator of Wright's fixation index (FST) and generation proxy selection mapping (GPSM). Hudson FST quantifies population-differentiation between groups, whereas GPSM detects selection signatures within a single population by regressing birth year on SNP genotypes. The aim of this study was to identify temporal allele frequency changes in SNPs consistent with selection during the genomic era and to evaluate their associations with milk production and fertility traits in Finnish Ayrshire. Genotypes were available for 64,160 cows across 46,914 SNPs, and phenotypic data on milk production and fertility traits were available for 49,417 genotyped individuals. Based on Hudson FST, 56 SNPs showed genetic differentiation between cows selected using pedigree-based and genomic information. In addition, 54 SNPs exhibited temporal allele frequency changes consistent with selection according to GPSM. Overall, 11 SNPs were identified by both methods. Of the 54 SNPs, thirteen were associated with the interval from first to last insemination in Finnish Ayrshire heifers. These results suggest that a substantial proportion of SNPs exhibiting temporal allele frequency changes during genomic selection are associated with heifer fertility.
Keywords: cattle; diversity; generation proxy selection mapping; genomic selection; selection signatures